Yona of the dawn. 26 - Kusanagi, Mizuho, 1979-; MacFarlane, Ysabet Reinhardt (Shojo beat manga., 2020)
"Princess Yona lives an ideal life as the only princess of her kingdom. Doted on by her father, the king, and protected by her faithful guard Hak, she cherishes the time spent with the man she loves, Su-won. But everything changes on her 16th birthday when tragedy strikes her family!... After unleashing their powers to save Yona, the Four Dragons lose consciousness and collapse! Su-won and the Kohka army arrive to participate in a summit with Xing, but Priest Gobi's anti-war faction members attack Princess Kouren! Can the nation of Xing achieve peace with all this infighting threatening its foundation?"--Provided by publisher.